1980
DOI: 10.1002/bem.2250010406
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of circulating antibody response of mice exposed to 9‐GHz pulsed microwaves

Abstract: A significant increase was observed in the circulating antibody titers of mice exposed to 9-GHz pulsed microwaves at an average power density of 10 mW/cm2, two hours per day for five days compared with sham-irradiated animals. The mice were previously immunized with type III pneumococcal polysaccharide. Following irradiation, a portion of the immunized animals were challenged with virulent Streptococcus pneumoniae, type III. Ten days after challenge, mortality was essentially the same in the two groups, but du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In many cases, thermal effects could account for the observed effects on immune cells as exemplified by the effect on natural killer cells, the activity of which is affected by temperature and/ or stress hormones (5,13,14). However, another study describing experiments conducted under isothermal conditions reported an increase in lymphocyte proliferation that was due to RF-radiation exposure and not to heating (15).…”
Section: Table 3 Expression Of Activation Markers In T and B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, thermal effects could account for the observed effects on immune cells as exemplified by the effect on natural killer cells, the activity of which is affected by temperature and/ or stress hormones (5,13,14). However, another study describing experiments conducted under isothermal conditions reported an increase in lymphocyte proliferation that was due to RF-radiation exposure and not to heating (15).…”
Section: Table 3 Expression Of Activation Markers In T and B Cellsmentioning
confidence: 99%
“…Despite this important consideration, there have been few in vivo experiments on the effects of microwave radiation from personal telecommunication devices on the immune system. Moreover, these few experiments showed some contrasting results and still leave open the question of whether RF radiation may affect the immune system (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%